2009
DOI: 10.1177/1744987108094813
|View full text |Cite
|
Sign up to set email alerts
|

Differences of hospitals’ organisational climates and nurses’ intent to stay: Nurses’ perspectives

Abstract: This research studied the differences of hospitals’ organisational climates and nurses’ intent to stay at different types of Jordanian hospitals and investigated the relationship between the two concepts, from the point views of nurses. In 2005, using convenience sampling technique, a survey was used to collect the data. A total of 361 nurses were recruited; 190 nurses from governmental hospitals, 107 nurses from teaching hospitals and 64 nurses from private hospitals. Comparisons were performed using the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…Besides, the study results were parallel to Kassem and Gaber [26] who found that nurses perceived their organizational climate positively. This finding is congruent with Giacomo [34]; Mryyan's [35] point of view. Unlike to this perspective, Van Bogaert et al, [36] indicated that nurses are dissatisfied with their work environment.…”
Section: Discussionsupporting
confidence: 91%
“…Besides, the study results were parallel to Kassem and Gaber [26] who found that nurses perceived their organizational climate positively. This finding is congruent with Giacomo [34]; Mryyan's [35] point of view. Unlike to this perspective, Van Bogaert et al, [36] indicated that nurses are dissatisfied with their work environment.…”
Section: Discussionsupporting
confidence: 91%
“…Structural empowerment needs to be achieved by increasing nurses’ access to resources, opportunities to learn and develop, support and information provided by the organizations, which will increase their commitment to the organization and thus their retention rate (Cai & Zhou 2009). Creating a ‘supportive work environment, with supportive leadership’ would give nurses the confidence to stay (Mrayyan 2009). Hospital administrators could communicate more with nurses, allowing more nurses to participate in managerial policy planning and goal setting, which in turn could improve their understanding of the vision and mission of the organization (Tsai & Wu 2010).…”
Section: Discussionmentioning
confidence: 99%
“…2009), which is often determined by the following factors: pay, advancement opportunity, workload and stress (Zeytinoglu et al. 2007), and satisfaction with their supervisor and organization (Mrayyan 2009). El‐Jardali et al.…”
Section: Introductionmentioning
confidence: 99%
“…Another study examining intent to stay surveyed nurses working in long‐term care homes and found similar results (McGilton et al., ). Liu and Liu () and Mrayyan () conducted survey‐based studies examining intent to stay in nonspecialty nurses who had been practising for a year or less and found perceived organizational culture, job satisfaction and leadership support as influencing factors. Most of the existing literature concerning both turnover and intent to stay focused on newer nurses working in generalized practice areas.…”
Section: Background and Literature Reviewmentioning
confidence: 99%